Tinjauan Etis Kristiani tentang Kekudusan Seksual Terhadap Praktik Sunat Sifon di Suku Atoni Meto, Nusa Tenggara Timur - Panjaitan, Firman; Boymau, Darius Arnoldus (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
Chiffon circumcision is a tradition of the Atoni Meto tribe. The practice of Siphon circumcision is unique because after a man undergoes circumcision, he must have sexual relations with another woman who is not his wife or permanent partner, intending to eliminate heat, dirt, or disease. Sexual intercourse is carried out to